Ataxia Telangiectasia: A Case Report - Sonia, Sheikh Farjana; Hassan, Mohammad Sayeed; Yusuf, Abdullah; Ara, Ferdous; Mojumder, SC (Journal of Shaheed Suhrawardy Medical College, 2017)
Ataxia telangiectasia (AT) is a complex multisystem disorder characterized by progressive neurological impairment, variable immunodeficiency and occulo-cutaneous telangiectasia. Ataxia telangiectasia is a member of chromosomal breakage syndromes and it is caused by a mutation in the ataxia-telangiectasia mutated (ATM) gene. We are reporting an eight year old girl of AT presented with difficulty in walking, frequent fall, trembling of the whole body, difficulty in speech. J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 41-43